Altered Cerebrospinal Fluid Clearance and Increased Intracranial Pressure in Rats 18 h After Experimental Cortical Ischaemia - Bothwell, Steven W.; Omileke, Daniel; Hood, Rebecca J.; Pepperall, Debbie-Gai; Azarpeykan, Sara; Patabendige, Adjanie; Spratt, Neil J. (Frontiers in Molecular Neuroscience, 2021)
Oedema-independent intracranial pressure (ICP) rise peaks 20-22-hours post-stroke in rats and may explain early neurological deterioration. Cerebrospinal fluid (CSF) volume changes may be involved. Cranial CSF clearance primarily occurs via the cervical lymphatics and movement into the spinal portion of the cranio-spinal compartment. We explored whether impaired CSF clearance at these sites could explain ICP rise after stroke. We recorded ICP at baseline and 18-hours post-stroke, when we expect changes contributing to peak ICP to be present. CSF clearance was assessed in rats receiving photothrombotic stroke or sham surgery by intraventricular tracer infusion. Tracer concentration was quantified in the deep cervical lymph nodes ex vivo and tracer transit to the spinal subarachnoid space was imaged in vivo. ICP rose significantly from baseline to 18-hours post-stroke in stroke vs sham rats (median = 5 mmHg, interquartile range (IQR) = 0.1 to 9.43, n=12, vs -0.3 mmHg, IQR = -1.9 to 1.7, n = 10), p=0.03. There was a bimodal distribution of rats with and without ICP rise. Tracer in the deep cervical lymph nodes was significantly lower in stroke with ICP rise (0 g/mL, IQR = 0 to 0.11) and without ICP rise (0 g/mL, IQR = 0 to 4.47) compared with sham rats (4.17 g/mL, IQR = 0.74 to 8.51), p=0.02. ICP rise was inversely correlated with faster CSF transit to the spinal subarachnoid space (R = -0.59, p=0.006, Spearman’s correlation). These data suggest that reduced cranial clearance of CSF via cervical lymphatics may contribute to post-stroke ICP rise, partially compensated via increased spinal CSF outflow.